A Study on Students’ Perceptions towards the Effectiveness of Teaching-Learning Strategies in an EFL Class: A Case Study at SMK Negeri 6 Kota Kupang in the Academic Year 2019/2020 - Rozita Yusniaty Lodo (Journal of English Education, Literature and Linguistics, 2021)
Abstract This study aimed at investigating the role of EFL teachers’ teaching strategies in their teaching effectiveness and their students’ motivation and achievement in learning English as a foreign language at SMK Negri 6 Kota Kupang. Data was collected by using a mixed-method with qualitative dominance. The students evaluated their teachers’ teaching effectiveness by completing the questionnaires distributed by the researcher. The findings suggested that the EFL students highly value respect and rapport from their teachers. Keywords: students’ perception, effective teaching strategies, EFL